Real Time Monitoring of Wireless Fire Detection Node. (2016) - Vijayalakshmi, S.R.; Muruganand, S.
Abstract: This work presents the design of low rate and low power sensor node in wireless based sensor network for early detection and monitoring of fire in environment. It uses the DHT11 digital temperature – humidity sensor for measurement and MSP430 microcontroller for processing and implementing best algorithm from the comparison algorithm and DST algorithm using Dempster-Shaffer Theory for fire detection. The detected information is transmitted to the computer system through XBeepro for short distance wirelessly. The performance of algorithms are analyzed and tested with the metric un_detect fire. The information is shared in real time to the owner/ fire station/ police and all other responsible persons by the computer system using teamviewer software through Internet. The DST has more software design complexity than comparison algorithm. But it gives better performance than comparison.